HUMAN RELATIONSHIPS IN THE WORKS OF D. H. LAWRENCE - Ibragimova Dilafruz Shukhratovna; Abdubannopova Nargizaxon Dilmurodjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article raises the topic of human relationships in D.H. Lawrence’s works. It will illustrate unusual connections between man and women. In addition, it gives the information about lots of criticism and literary works which were about controversial matters in people’s lifestyle.